Dynamic relationships between depressive symptoms and insulin resistance over 20 years of adulthood. Issue 4 (7th March 2023) - Wu, Che-Yuan; Cogo-Moreira, Hugo; MacIntosh, Bradley J.; Edwards, Jodi D.; Krance, Saffire H.; Eid, Michael; Schreiner, Pamela J.; Launer, Lenore J.; Swardfager, Walter
Abstract: Background: Bidirectional longitudinal relationships between depression and diabetes have been observed, but the dominant direction of their temporal relationships remains controversial. Methods: The random-intercept cross-lagged panel model decomposes observed variables into a latent intercept representing the traits, and occasion-specific latent 'state' variables. This permits correlations to be assessed between the traits, while longitudinal 'cross-lagged' associations and cross-sectional correlations can be assessed between occasion-specific latent variables. We examined dynamic relationships between depressive symptoms and insulin resistance across five visits over 20 years of adulthood in the population-based Coronary Artery Risk Development in Young Adults (CARDIA) study. Possible differences based on population group (Black v. White participants), sex and years of education were tested. Depressive symptoms and insulin resistance were quantified using the Center for Epidemiologic Studies Depression (CES-D) scale and the homeostatic model assessment for insulin resistance (HOMA-IR), respectively. Results: Among 4044 participants (baseline mean age 34.9 ± 3.7 years, 53% women, 51% Black participants), HOMA-IR and CES-D traits were weakly correlated ( r = 0.081, p = 0.002). Some occasion-specific correlations, but no cross-lagged associations were observed overall. Longitudinal dynamics of these relationships differed by population groups such that HOMA-IR at age 50 was associated with CES-D score at age 55 ( β = 0.076, p = 0.038) in White participants only. Longitudinal dynamics were consistent between sexes and based on education. Conclusions: The relationship between depressive symptoms and insulin resistance was best characterized by weak correlations between occasion-specific states and enduring traits, with weak evidence that insulin resistance might be temporally associated with subsequent depressive symptoms among White participants later in adulthood.